Pengumpulan Data Biotik Dalam Studi Lingkungan Kuna - nfn. Siswanto (Berkala Arkeologi, 1995)
The natural history of the environment can be studied through environmental resources (physical and biotic) along with archaeological resources. Thus, the role of archaeological studies as a support in environmental studies is clear so that this can be the other way around, for the sake of archaeological studies it is necessary to support it by carrying out past environmental studies.